Perbedaan Kematangan Emosi Remaja Ditinjau Dari Bentuk Pola Asuh Orangtua - Putri, Nabilla; Primanita, Rida Yanna (CAUSALITA : Journal of Psychology, 2024)
During adolescence, a person will go through several phases with varying levels of difficulty in their developmental tasks. Adolescence is a developmental period that is closely related to emotional problems. This research aims to determine the description of emotional maturity in adolescents, to understand the description of parenting patterns applied to adolescents. To determine the differences in emotional maturity of adolescents in terms of the form of parental parenting. This research uses quantitative research methodology, this research is descriptive in nature. Descriptive research is a research method that attempts to describe, describe and interpret objects as they are without intending to draw conclusions that apply to the general public. The population used in this research is teenagers who have the characteristics of teenagers aged 13-18 years, living with their parents/guardians and also domiciled in Bukittinggi. There were 80 teenagers in this study Data collection instruments were created in natural and technical conditionsThe data collection is based more on internal statements scale and questionnaire form. Based on hypothesis testing using the Kruskal Wallis test in SPSS, Asymp results were obtained. Sig is 0.012. This value is smaller than 0.05 so it can be said that H0 is accepted and Ha is rejected, which means there is no difference in the emotional maturity of teenagers in terms of the form of parenting applied by parents.